Manajemen Budaya Mutu Untuk Pengembangan Kecerdasan Holistik Siswa Sekolah Dasar Islam - Imroatul Mufidata, Ana; Yasin, Muhammad (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
According to Goleman’s research, a person’s success is influenced 80% more by emotional intelligence than intellectual intelligence. This research aims to describe the management of quality culture at SDI NU Pare Kediri, an Islamic elementary school, in developing students' holistic intelligence, including intellectual, emotional, and spiritual aspects, built upon the foundation of the teachers’ “manajemen of the heart” approach. This type of research is a case study using a qualitative approach with in-depth interview techniques, observation, and documentation. The results of this research indicate that: (1) the management of quality culture at SDI NU Pare Kediri has implemented the functions of POAC management, complemented by innovative school programs that support the development of students’s holistic intelligence and are carried out with high commitment and consistency (istiqomah). (2) The holistic intelligence of SDI NU Pare Kediri students has developed well, including IQ, as shown by academic and non-academic achievements and graduation results, EQ, as evidenced by good attitudes, manners, morals, self-confidence, and strong learning resilience, and SQ, which develops according to their age, students have graduated with mastery of reciting the Qur'an, memorization of up to 8 chapters, mastering recitations for special occasions, and being aware of prayer.